2013
DOI: 10.1080/17470218.2012.750677
|View full text |Cite
|
Sign up to set email alerts
|

Wait a second: Brief delays in responding reduce focality effects in event-based prospective memory

Abstract: Remembering to perform deferred actions when an event is encountered in the future is referred to as event-based prospective memory (PM). We examined whether the failure of individuals to allocate sufficient attentional resources to nonfocal PM tasks can be linked to the response demands inherent in PM paradigms that require the PM task to race for response selection with the speeded ongoing task. In three experiments, participants performed a lexical decision task while being required to make a separate PM re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
117
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(133 citation statements)
references
References 43 publications
13
117
3
Order By: Relevance
“…Therefore, an appropriate conceptualization of focal versus nonfocal PM may not be a distinction between automatic or spontaneous versus controlled processing of PM, but rather a more fine-grained perspective that considers the coexisting contribution of automatic and controlled processes within the different process phases of PM. This may also help to explain the mixed results across studies comparing focal versus nonfocal PM performance (e.g., Loft & Remington, 2013;Rendell et al, 2007;Vogels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an appropriate conceptualization of focal versus nonfocal PM may not be a distinction between automatic or spontaneous versus controlled processing of PM, but rather a more fine-grained perspective that considers the coexisting contribution of automatic and controlled processes within the different process phases of PM. This may also help to explain the mixed results across studies comparing focal versus nonfocal PM performance (e.g., Loft & Remington, 2013;Rendell et al, 2007;Vogels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, it has been suggested that costs may instead arise because the PM task races and competes for response selection with the more routine ongoing task, and to ensure that an ongoing task response is not made in lieu of a PM response, participants delay ongoing task responding to allow more time for PM evidence to accumulate (termed delay theory ; Loft & Remington, 2013). That is, the delay theory posits that PM information (e.g., whether the stimulus contains the syllable tor ) accrues in parallel with ongoing task information (e.g., stimulus lexicality) but at a slower rate, and so delaying ongoing task responding allows more time for PM information to accumulate and increases the likelihood of the appropriate response (e.g., “7” key) being selected.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we evaluate this question by using an experimental delayed response PM paradigm developed by Loft and Remington (2013). This paradigm aims to examine whether difficulties in remembering to perform non-focal PM tasks are due -- at least in part -- to the competing rapid response demands of the more habitual and speeded ongoing task.…”
mentioning
confidence: 99%